Computer simulator for student training to effective exploitation the catalytic cracking unit; Petroleum and Coal; Vol. 58, iss. 1 - Nazarova G. Yu. Galina Yurievna; Burumbaeva G. R. Galiya Rashidovna; Shafran T. A. Tatjyana Aleksandrovna; Svarovsky A. Ya. Aleksandr Yakovlevich (2016, 2016)
Title screen